Training to Become Creative English Teachers and Millennials: Teaching and Learning Into The Digital Era - Amiruddin; Hasbi, Muhammad; Latif, Fatmawati; Lerfiana, Ema; Sri Widistari, Besse (Education and Talent Development Center of Indonesia, 2022)
This commitment is inspired by the instructors in Wajo Regency, who are still many who have not been affected by technology and their English teaching methods are regarded as monotonous. As a result, training is required to impart knowledge about creative and millennial teachers. The goal of this service activity is to train and execute the habit of English teachers in Wajo Regency to become creative and millennial instructors as part of the industrial revolution 4.0 implementation. Creative is not only skilled in the use of media, but also in the application of proper English teaching methods or strategies. The service method is used to carry out this activity in the form of teaching, training, and evaluation. This trial project is associated with the Education Office in South Sulawesi Province and educational institutions in Wajo Regency, particularly the Sengkang Junior High School. The education office and allied organizations have the same objective as the team performing this community service project, which is to educate the Indonesian nation's life. This community service evaluation activity is related to everything that happens during the implementation process. This begins with preliminary planning, which includes field observations at Wajo District Junior High Schools.